Research on AE Source Location of Linear and Plane Rock Mass - Haiyan Wang; Ji Ma; Gongda Wang; Han Gao; Guangyong Cui; Xiaoshen Li (Shock and Vibration)
The occurrence of rockburst dynamic disaster is a process from the microdamage to macroinstability of coal and rock mass, which is accompanied by the acoustic emission (AE) phenomenon. The application of AE technology can reliably help to judge and predict the damage evolution of coal and rock mass, as the most basic problem in the study of AE is the location of the AE source. In this work, the AE source localization experiments of rod-shaped rocks and plate-shaped rocks were carried out. The influence of calibration wave velocity of linear and plane positioning on the location of the AE source was studied. The feasibility analysis of the AE source localization of a plate-shaped rock with different sensor arrays was conducted. The result of the plane location was optimized by wavelet packet analysis combined with cross correlations. The results show that the homogeneity of marble members in this work is suitable, and the positioning error is least affected by wave velocity. In the positioning of the plane AE source, it is suitable to choose a diamond sensor array. The positioning source should be located near the center of the array network. The positioning effect of the rod-shaped rock is generally better than that of the plate-shaped rock. In the actual source positioning work, it should be simplified as much as possible as a linear positioning problem. A more accurate AE signal delay could be obtained using wavelet packet analysis combined with cross-correlation technology, which can greatly reduce the positioning error caused by the accuracy of time difference. The purpose of this work is to provide a basis for determining a more accurate location of the fracture source of rock materials, which is of great significance and application value on the prediction and control of rockburst dynamic disaster.